Changing Patterns of Global Trade - Riad, Nagwa (Departmental Papers; Departmental Paper, 2012)
Changing Patterns of Global Trade outlines the factors underlying important shifts in global trade that have occurred in recent decades. The emergence of global supply chains and their increasing role in trade patterns allowed emerging market economies to boost their inputs in high-technology exports and is associated with increased trade interconnectedness.The analysis points to one important trend taking place over the last decade: the emergence of China as a major systemically important trading hub, reflecting not only the size of trade but also the increase in number of its significant trading partners.